STUDY OF THE DUSTY SOLID FUEL COMBUSTION AND THE INFLUENCE OF ITS INDIVIDUAL PROPERTIES ON THE COURSE OF THE COMBUSTION INITIAL STAGES (Modern Problems of Metallurgy, 2024)
The article discusses separate methodological approaches to modeling the combustion of pulverized fuel in laboratory conditions, which have been developed over the past decades, and separate results of research into the combustion of individual particles using high-speed photo and video recording. It is shown that today clear ideas have been formed regarding the process of burning both individual fuel particles and their burning in a torch. It is noted that for some types of fuel, the division of the combustion process of particles into stages is very conditional, because due to the nature (origin) of the fuel raw materials, individual stages may overlap one another or be absent altogether. The thesis is put forward that, regardless of the criteria for the efficiency of fuel use, for the development of the most effective technologies for its combustion, not only the specifics (conditions) of certain units and processes, but also the nature (origin) of the fuel raw materials used, as it directly determines physics and chemistry of the combustion process. The authors experimentally confirmed a close relationship between the ignition temperature of the fuel and the release of volatile substances from it, in particular, it was found that the ignition temperature of the fuel functionally depends on the content of CO in volatile substances, the release of which from the fuel can be one of the important criteria when assessing its flammability. The thesis is put forward about the expediency of using the "ignition temperature" parameter as such, which should be taken into account (and in some cases - determined), since it is closely related to both the time to ignition of fuel particles and the completeness of its combustion in the initial stages, which was proved experimentally.
Keywords: pulverized fuel; stages of combustion; single fuel particles; biofuel; release of volatile substances; ignition temperature; completeness of combustion